Fatigue life of GMAW and PAW welding joints of boron microalloyed steels - Svoboda, Hernán Gabriel (2015)
Recently boron microalloyed steels have become an alternative in weight saving in structural elements in automotive industry,especially for parts like pillars and columns and reinforcements. These materials are used as quenched and tempered, reachingstrength values between 1000 and 1500 MPa. Welding is a relevant issue as a fabrication process in automotive industry, inparticular for high strength steels. Furthermore, fatigue life of these welded joints plays a very important role for theseapplications. Gas metal arc welding (GMAW) is one of the more widely used welding processes in automotive industry. Indeed,different aspects of plasma arc welding (PAW) make it an interesting option for these applications. The objective of this workwas to evaluate the fatigue life of GMAW and PAW welded joints of boron microalloyed steels, in a quenched and temperedcondition. Samples of 100×100 mm were butt welded by GMAW and PAW and microstructural and mechanically characterized.Fatigue curves were obtained for both processes in a four point bending configuration. It was observed that PAW welded sampleshad a higher fatigue life than those welded by GMAW. Weld bead toes of GMAW joints acted as geometric stress concentrators,being the main responsible for fatigue resistance reduction.